Retrieval Practice Fails to Insulate Episodic Memories against Interference after Stroke - Pastötter, Bernhard; Eberle, Hanna; Aue, Ingo; Bäuml, Karl-Heinz T. (Frontiers in Psychology, 2017)
Recent work in cognitive psychology showed that retrieval practice of previously studied information can insulate this information against retroactive interference from subsequently studied other information in healthy individuals. The present study examined whether this beneficial effect of interference reduction is also present in patients with stroke. Twenty-two patients with stroke, 4.6 months post injury on average, and 22 healthy controls participated in the experiment. In each of two experimental sessions, participants first studied a list of items (list 1) and then underwent a practice phase in which the list 1 items were either restudied or retrieval practiced. Participants then either studied a second list of items (list 2) or fulfilled an unrelated distractor task. Recall of the two lists’ items was assessed in a final criterion test. Results showed that, in healthy controls, additional study of list 2 items impaired final recall of list 1 items in the restudy condition but not in the retrieval practice condition. In contrast, in patients with stroke, list 2 learning impaired final list 1 recall in both conditions. The results indicate that retrieval practice insulated the tested information against retroactive interference in healthy controls, but failed to do so in patients with stroke. Possible implications of the findings for the understanding of long-term memory impairment after stroke are discussed.